1987
DOI: 10.1016/0028-3908(87)90228-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of footshock stress on regional brain dopamine metabolism and pituitary β-endorphin release in rats previously sensitized to amphetamine

Abstract: The repeated intermittent administration of amphetamine (AMP) produces an enduring enhancement in the response of dopamine (DA) systems in the brain to a subsequent "challenge" with amphetamine. However, former amphetamine addicts are not only hypersensitive to amphetamine, but also to "physical or psychological stress". This suggests that sensitization to amphetamine may change the response of DA neurons in brain to subsequent stress. To explore this idea, the effects of footshock stress on regional metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

1988
1988
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(47 citation statements)
references
References 67 publications
(4 reference statements)
4
42
0
1
Order By: Relevance
“…This stress sensitization may help explain why psychosis only recurs in subjects with a history of AMP psychosis following exposure to stress. 9 Previous exposure to stressful stimuli induces noradrenergic hyperreactivity to subsequent mild stress. 10 Stress-induced noradrenergic hyperactivity may be a precipitating factor in stressrelated psychiatric disorders.…”
Section: Spontaneous Recurrence Of Methamphetamine Psychosismentioning
confidence: 99%
See 2 more Smart Citations
“…This stress sensitization may help explain why psychosis only recurs in subjects with a history of AMP psychosis following exposure to stress. 9 Previous exposure to stressful stimuli induces noradrenergic hyperreactivity to subsequent mild stress. 10 Stress-induced noradrenergic hyperactivity may be a precipitating factor in stressrelated psychiatric disorders.…”
Section: Spontaneous Recurrence Of Methamphetamine Psychosismentioning
confidence: 99%
“…The present findings on plasma monoamine metabolite levels suggest that increased noradrenergic activity be related to the occurrence of flashbacks. Considering that stressful stimuli induce noradrenergic hyperreactivity to subsequent stress, 10 and that AMP induced enduring sensitization to stress, 9,15 threatening experiences together with MAP use may have increased sensitivity to subsequent exposure to similar but less severe situations, so that heightened NE release may have been elicited in response to a mild fear of other people. It has been documented that 3-MT levels in the rat brain serve as a sensitive index of dopamine release.…”
Section: Increased Sensitivity To Stress Associated With a Predominanmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were homogenized and centrifuged at 1500g for 4 minutes. The supernatant was flltered and assayed by HPLC and electrochemical de tection using procedures similar to those described pre viously (Robinson et al 1987).…”
Section: Assay For Monoaminesmentioning
confidence: 99%
“…It has been well known that both footshock stress and restraint stress elevate the plasma concentration of catecholamines. [19][20][21] Rossier et al and Robinson et al have also reported that footshock stress significantly elevates the plasma concentration of b-endorphin, 22,23) whereas Williams et al have reported that the restraint stress only slightly elevates plasma b-endorphin concentration. 13) We also observed that the increase in plasma bendorphin after footshock stress was higher than that after restraint stress (data not shown).…”
Section: Discussionmentioning
confidence: 99%